Stagnasi dalam Hukum Keluarga Islam di Indonesia - Holan Riadi (LP3M STITNU AL HIKMAH MOJOKERTO, 2020)
Islamic family law in Indonesia has become one of the changes in the legal culture that has occurred from time to time. One of these stagnations is the application of Islamic law to various theories, thus making the Arabization of Islam. This makes the stagnation of Islamic family law in Indonesia undergo renewal. This reform is one of the things that gave birth to various schools that can be used as benchmarks in Islamic family law. The purpose of this study is to explain the stagnation in Islamic family law in Indonesia that has been born since ancient times. This study uses qualitative research methods with descriptive-analysis type. The results of this study are expected that Islamic family law will move forward, followed by the development of acculturation in various regions in Indonesia.